Reversible Image Data Hiding Using Encryption and Decryption with Contrast Enhancement - Raj, Asha S; Nair P, Mrs.Gayathri (IJRDO -Journal of Computer Science Engineering, 2016)
The Reversible Data Hiding of image UsingEncryption and Decryption with Contrast Enhancement isa widely used technique. Recoverence of host image isdone. Using Encryption and Decryption with ContrastEnhancement. It is applied at medical and militaryapplications. The data embedding continous loss isinevitable. In several areas such as medical, military, andlaw forensics degradation of cover image is not allowed.For the sake of Reversible Image Data Hiding UsingEncryption and Decryption with Contrast Enhancement.The main applications are medical and military areas. Thedigital images that embeds data into image. Forcommunication seceret maintenance alteration of pixel ismuch needed. Reversible Image Data Hiding UsingEncryption and Decryption for high security andefficiency. It enables images to data in hidden format.Restoration process is focused. The Reversible Image DataHiding Using Encryption and Decryption with ContrastEnhancement which uses the encryption and decryptionfor enhancing the security of the whole system.